Enlightenment, modernity and democracy: : Leo Strauss, H. L. Mencken and the new political science - Pearce, Colin (Dia-noesis: A Journal of Philosophy, 2024)
This essay seeks to demonstrate a certain overlap between the political thought of Leo Strauss (1899-1973) and H. L. Mencken (1888-1956). The argument fully recognizes that Strauss is a political philosopher inclined to the classics and natural right, and Mencken is a journalist inclined to the moderns and the power of scientific progress, they nevertheless occupy the same terrain in respect of certain opinions on the purely political plane. Allowing a great distance between the two men philosophically speaking, we can still see them come together in arguing that a regime which looks up to certain individuals of ability, talents, character, intellect and virtue has to be the standard by which the discipline of political science makes its judgments concerning the phenomena of political life.